Systematic literature review: Analysis potential implementation of STEAM in the Merdeka Curriculum for senior high school biology - Nurul Faizah; Slamet Suyanto; Nurul Hidayat (Master Program of Biology Education, Universitas Lambung Mangkurat, Banjarmasin, Indonesia, 2026)
Science, Technology, Engineering, Arts, and Mathematics (STEAM) learning is an educational approach that integrates science, technology, engineering, art, and mathematics to address real-life problems. It aims to develop students’ critical, creative, communicative, and collaborative skills in line with 21st-century competencies. This study aims to explore the potential and reported trends of implementing STEAM in the Independent Curriculum in biology learning in Indonesia, particularly in underdeveloped areas, rather than to determine its direct effectiveness. A Systematic Literature Review (SLR) was conducted using Google Scholar to identify relevant articles published between 2018 and 2024. The selection process involved screening for relevance to STEAM-based learning in biology and applying inclusion criteria such as focus on senior high school education and Indonesian context. Out of 10 selected articles, the analysis was performed using thematic synthesis to identify common patterns and trends. The results indicate that the Independent Curriculum has the potential to support STEAM-based learning, even in disadvantaged areas, and that this integration can foster the development of students’ competencies in accordance with 21st-century learning goals.Abstrak. Pembelajaran Science, Technology, Engineering, Arts, and Mathematics (STEAM) adalah pendekatan pendidikan yang mengintegrasikan sains, teknologi, teknik, seni, dan matematika untuk mengatasi masalah kehidupan nyata. Tujuannya adalah untuk mengembangkan keterampilan kritis, kreatif, komunikatif, dan kolaboratif siswa sesuai dengan kompetensi abad ke-21. Studi ini bertujuan untuk mengeksplorasi potensi dan tren yang dilaporkan dari implementasi STEAM dalam Kurikulum Independen dalam pembelajaran biologi di Indonesia, khususnya di daerah yang kurang berkembang, daripada untuk menentukan efektivitas langsungnya. Tinjauan Pustaka Sistematis (SLR) dilakukan menggunakan Google Scholar untuk mengidentifikasi artikel-artikel relevan yang diterbitkan antara tahun 2018 dan 2024. Proses seleksi melibatkan penyaringan relevansi dengan pembelajaran berbasis STEAM dalam biologi dan penerapan kriteria inklusi seperti fokus pada pendidikan SMA dan konteks Indonesia. Dari 10 artikel terpilih, analisis dilakukan menggunakan sintesis tematik untuk mengidentifikasi pola dan tren umum. Hasil menunjukkan bahwa Kurikulum Independen memiliki potensi untuk mendukung pembelajaran berbasis STEAM, bahkan di daerah yang kurang beruntung, dan integrasi ini dapat mendorong pengembangan kompetensi siswa sesuai dengan tujuan pembelajaran abad ke-21.